A Systematic Review of Advocacy Curricula in Graduate Medical Education - Howell, Benjamin A.; Kristal, Ross B.; Whitmire, Lacey R.; Gentry, Mark; Rabin, Tracy L.; Rosenbaum, Julie (Journal of general internal medicine : JGIM, 2019)
Background Professionalism standards encourage physicians to participate in public advocacy on behalf of societal health and well-being. While the number of publications of advocacy curricula for GME-level trainees has increased, there has been no formal effort to catalog them. Objective To systematically review the existing literature on curricula for teaching advocacy to GME-level trainees and synthesize the results to provide a resource for programs interested in developing advocacy curricula. Methods A systematic literature review was conducted to identify articles published in English that describe advocacy curricula for graduate medical education trainees in the USA and Canada current to September 2017. Two reviewers independently screened titles, abstracts, and full texts to identify articles meeting our inclusion and exclusion criteria, with disagreements resolved by a third reviewer. We abstracted information and themes on curriculum development, implementation, and sustainability. Learning objectives, educational content, teaching methods, and evaluations for each curriculum were also extracted. Results After reviewing 884 articles, we identified 38 articles meeting our inclusion and exclusion criteria. Curricula were offered across a variety of specialties, with 84% offered in primary care specialties. There was considerable heterogeneity in the educational content of included advocacy curriculum, ranging from community partnership to legislative advocacy. Common facilitators of curriculum implementation included the American Council for Graduate Medical Education requirements, institutional support, and preexisting faculty experience. Common barriers were competing curricular demands, time constraints, and turnover in volunteer faculty and community partners. Formal evaluation revealed that advocacy curricula were acceptable to trainees and improved knowledge, attitudes, and reported self-efficacy around advocacy. Discussion Our systematic review of the medical education literature identified several advocacy curricula for graduate medical education trainees. These curricula provide templates for integrating advocacy education into GME-level training programs across specialties, but more work needs to be done to define standards and expectations around GME training for this professional activity.